Pemodelan TEC Regional dari Data GPS Stasiun Tetap di Indonesia dan Sekitarnya - Buldan Muslim; Hasanuddin Z. Abidin; The Houw Liong; Wedyanto Kuntjoro; Cecep Subarya; Heri Andreas; M. Gamal (Institute for Research and Community Services (LPPM) ITB, 2006)
Ionosphere affect propagation of electromagnetic waves through it by adding a transmission delay time. In GPS positioning and navigation, ionospheric delay is largest source of error after error from Selective Availability (SA) was turned off. For GPS positioning precisely ionospheric effect must be estimated so ionospheric correction can be determinated to eliminate ionospheric effect on GPS observation. In positioning by using GPS single frequency, ionospheric correction can be obtained from GPS dual frequency receiver at reference station or model. This paper describes method of determination and modeling of regional total electron content (TEC) from continuous GPS station in Indonesia and it's around. Spatial model of TEC at certain time is estimated by using polynomial function. Diurnal variation of polynomial model coefficient at certain hour from 00.00